Respuesta :
Step 1: Rewrite equations
2x - 3y = 16
5x - 3y = 13
Step 2: To be able to eliminate, multiply the second equation by -1
-1(5x - 3y = 13) —> -5x+3y=-13
Step 3: Use the elimination method to solve, using new equation
2x-3y=16
-5x+3y=-13
_________
-3x=3
x=-1
Step 4: Using x, substitute it into an equation for y
2x - 3y = 16
2(-1) - 3y =16
-2 -3y =16
+2 +2
________
-3y=18
y=-6
Final answer: A) (-1,-6)
2x - 3y = 16
5x - 3y = 13
Step 2: To be able to eliminate, multiply the second equation by -1
-1(5x - 3y = 13) —> -5x+3y=-13
Step 3: Use the elimination method to solve, using new equation
2x-3y=16
-5x+3y=-13
_________
-3x=3
x=-1
Step 4: Using x, substitute it into an equation for y
2x - 3y = 16
2(-1) - 3y =16
-2 -3y =16
+2 +2
________
-3y=18
y=-6
Final answer: A) (-1,-6)